Modern political science : Anglo-American exchanges since 1880 - Adcock, Robert, 1974-; Bevir, Mark; Stimson, Shannon C. (Princeton paperbacks., 2007)
Since emerging in the late nineteenth century, political science has undergone a radical shift--from constructing grand narratives of national political development to producing empirical studies of individual political phenomena. What caused this change? Modern Political Science--the first authoritative history of Anglophone political science--argues that the field's transformation shouldn't be mistaken for a case of simple progress and increasing scientific precision.